Early-age heat evolution of clinker cements in relation to microstructure and composition: Implications for temperature development in large concrete elements. - Ballim, Y.; Graham, P.C. (Elsevier, 2004)
This paper presents an assessment of the range and extent of variation of heat evolution of nominally similar cement clinkers from a range of cement production facilities in South Africa. Clinker samples were collected at nine cement plants and cements were prepared by grinding each clinker with a uniform quality of gypsum. X-ray fluorescence and optical microscope techniques were then used to characterise each clinker and cement in terms of chemical composition and cement compound morphology. Concretes were then prepared with the laboratory-manufactured cements and these were tested in an adiabatic calorimeter in order to determine the rate of heat evolution from each of the clinker samples. The results of these tests were related to the chemical and morphological characteristics of the corresponding cement clinkers. The results indicate a clear differentiation of clinker cements into low, medium and high heat cements. The relationships between this classification of the heat performance of the cements and the chemistry and morphology of the clinker is not clear at this stage. However, using a finite difference heat model, the paper presents an indication of the implications of the measured heat characteristics of the cement for early-age temperature distributions in large concrete elements.
Keywords: Cement; Chemistry; Clinker; Fineness; Heat; Mass concrete; Microscopy; Modelling; Morphology; Hydration; Fluorescence